Features of thermo- and electromyography in patients with vertebrogenic pain syndrome - E. S. Tsyslyak; E. G. Ippolitova; T. K. Verkhozina; O. V. Sklyarenko; S. D. Glotov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
Thermography and electroneuromyography parameters were studied in 34 patients with vertebrogenic pain syndrome associated with lumbar spine stenosis. All patients were treated in the neurosurgical department of the Irkutsk Scientific Centre of Surgery and Traumatology. We determined the changes in temperature values in the lumbar spine and lower extremities under the condition of disorder in peripheral nerves functional state.Purpose of the study: to evaluate the parameters of thermography and electroneuromyography in patients with lumbar spine stenosis.Materials and methods. The article presents the results of thermography and electroneuromyography of 34 patients with severe pain syndrome associated with degenerative stenosis of the lumbar part of spinal canal in preoperative period. Thermal-imaging study was carried out using a thermovision camera SVIT-004, the study of the peripheral nerves function of the lower extremities was carried out using the Neuromian-1-04 neuromyoanalyzer. The skin temperature recording points corresponded to the projection of stimulating and pickup ENMG electrodes on the spinous processes of the LIV, LV, SI vertebrae and paravertebrally.Results. Thermography parameters in patients with degenerative lumbar spine stenosis on the pain side were higher than on the intact side at all measurement points by 1–2 °C. At the same time, electroneuromyographic parameters in these patients indicated a decrease in the activity of the peripheral and central motor apparatus.Conclusion. The change in thermography parameters in patients with lumbar spine stenosis in the lumbar part and the area of pain irradiation in the lower extremities occurs alongside with the disorder of the peripheral nerves functional state.